Short and long-term impact of adolescent pregnancy on postpartum contraceptive use: implications for prevention of repeat pregnancy. - Kershaw, Trace S; Niccolai, Linda M; Ickovics, Jeannette R; Lewis, Jessica B; Meade, Christina S; Ethier, Kathleen A (The Journal of adolescent health : official publication of the Society for Adolescent Medicine, 2003)
To describe patterns and changes in contraceptive use among pregnant adolescents in early and later postpartum compared with nonpregnant adolescents.
Keywords: Adolescent; Condoms; Connecticut; Contraception Behavior; Contraceptives, Oral, Hormonal; Family Planning Services; Female; Follow-Up Studies; Humans; Interviews as Topic; Male; Mothers; Postpartum Period; Pregnancy; Pregnancy in Adolescence; Regression Analysis; Socioeconomic Factors